Tasman Sea high‐ and low‐ chlorophyll events, their links to marine heat waves, cool spells, and global teleconnections - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2023)
Previous work has suggested that marine heat waves (MHW) and cool spells (MCS) in the Tasman Sea are responses to a stalling of an eastward propagating austral wavenumber‐4 atmospheric pressure wave. We investigate extrema in sea surface chlorophyll (SSC), defining high‐ and low‐chlorophyll events (HCE and LCE) analogous to MHW and MCS, but using Tasman‐Sea averaged SSC anomalies. From 2002 to 2020, there were 13 HCE and 10 LCE, with no indication of changes in frequency, duration, or intensity of events. HCE tend to occur when Tasman‐Sea averaged sea surface temperature is anomalously cool, and LCE tend to occur when Tasman‐Sea averaged surface temperature is anomalously warm, however, there is no direct relationship between temperature and chlorophyll extrema. Canonical HCE/LCE formed from the 2002 to 2020 events suggest that HCE/LCE are also driven by the austral wavenumber‐4 atmospheric wave. HCE occur during periods of low wind stress after a period of increased wind stress, whereas LCE may be a result of strong vertical mixing that mixes surface phytoplankton downwards. The implications of this work are that changes in Tasman Sea primary production in a future ocean will depend on any changes in the wavenumber‐4 atmospheric wave.

What Impact Does Participation in a Communication Skills Training Program Have on Health Professionals’ Communication Behaviors: Findings from a Qualitative Study - V. White; M. Chiswell; E. Webber; P. Martin; A. Piper (Journal of Cancer Education, 2023)
Communication skills training can enhance health professionals’ knowledge and repertoire of effective communication practices. This paper describes the conceptual model underlying a 3-day retreat communication skills training program, methods used for training, and participant perception of outcomes from the training using qualitative interviews. Repeated qualitative telephone interviews (approximately 6 months apart) with participants of a 3-day Clinical Consultation Skills Retreat. Fourteen participants (70% response, 57% doctors) took part at Time 1, with 12 participating at Time 2. Semi-structured interviews were recorded and transcribed, and directional content analysis was conducted to assess themes in areas of key learnings, implementation of skills, and barriers. The training was received very positively with participants valuing the small group learning, role play, and facilitator skills. Key learnings were grouped into two themes: (i) tips and strategies to use in clinical practice and (ii) communication frameworks/methods, with the second theme reflecting an awareness of different communication styles. Most participants had tried to implement their new skills, with implementation reported as a more deliberate activity at T1 than at T2. Those implementing the new skills noted more open conversations with patients. Practical barriers of lack of time and expectations of others were mentioned more often at T2. A 3-day retreat-based communication training program was positively received and had a positive impact on the use of new communication skills. While further work is needed to determine whether effects of training are evidenced in objective clinical behaviors, the positive longer-term benefits found suggest this work would be worthwhile.

Trace Metal Dynamics in Shallow Hydrothermal Plumes at the Kermadec Arc - Charlotte Kleint; Rebecca Zitoun; René Neuholz; Maren Walter; Bernhard Schnetger; Lukas Klose; Stephen M. Chiswell; Rob Middag; Patrick Laan; Sylvia G. Sander; Andrea Koschinsky (Frontiers in Marine Science, 2022)
Hydrothermal vents are a source of many trace metals to the oceans. Compared to mid-ocean ridges, hydrothermal vent systems at arcs occur in shallower water depth and are much more diverse in fluid composition, resulting in highly variable water column trace metal concentrations. However, only few studies have focused on trace metal dynamics in hydrothermal plumes at volcanic arcs. During R/V Sonne cruise SO253 in 2016/2017, hydrothermal plumes from two hydrothermally active submarine volcanoes along the Kermadec arc in the Southwest Pacific Ocean were sampled: (1) Macauley, a magmatic dominated vent site located in water depths between 300 and 680 m, and (2) Brothers, located between 1,200 and 1,600 m water depth, where hydrothermalism influenced by water rock interactions and magmatically influenced vent sites occur near each other. Surface currents estimated from satellite-altimeter derived currents and direct measurements at the sites using lowered acoustic Doppler current profilers indicate the oceanic regime is dominated by mesoscale eddies. At both volcanoes, results indicated strong plumes of dissolved trace metals, notably Mn, Fe, Co, Ni, Cu, Zn, Cd, La, and Pb, some of which are essential micronutrients. Dissolved metal concentrations commonly decreased with distance from the vents, as to be expected, however, certain element/Fe ratios increased, suggesting a higher solubility of these elements and/or their stronger stabilization (e.g., for Zn compared to Fe). Our data indicate that at the magmatically influenced Macauley and Brothers cone sites, the transport of trace metals is strongly controlled by sulfide nanoparticles, while at the Brothers NW caldera wall site iron oxyhydroxides seem to dominate the trace metal transport over sulfides. Solution stabilization of trace metals by organic complexation appears to compete with particle adsorption processes. As well as extending the generally sparse data set for hydrothermal plumes at volcanic arc systems, our study presents the first data on several dissolved trace metals in the Macauley system, and extends the existing plume dataset of Brothers volcano. Our data further indicate that chemical signatures and processes at arc volcanoes are highly diverse, even on small scales.

Long‐term trends in the frequency and magnitude of upwelling along the West Coast of the South Island, New Zealand, and the impact on primary production - Stephen M. Chiswell; Joanne M. O’Callaghan (New Zealand Journal of Marine and Freshwater Research, 2021)
Satellite‐derived estimates of sea surface temperature (SST), chlorophyll (Chl), and fluorescence line height (FLH), from 22 sites ∼20 km offshore from the West Coast of the South Island, New Zealand (WCSI) are used to investigate long‐term trends in SST, the frequency and magnitude of cool and warm events, and their impacts on SSC and FLH. WCSI trends have been towards higher temperature and less chlorophyll, with a 0.83°C rise in mean along‐shore SST since 1982, and a 0.1 mg Chl m −3 drop in mean along‐shore SSC since 2002. With respect to the trend, there were 13 extreme cool and 14 extreme warm events between 1982 and 2019, with mean values of −2.55 and 2.62°C, respectively. There was no measurable change in the frequency of extreme events, but there is a suggestion that extreme events are becoming warmer. During extreme events, Chl and FLH show inverse relationships with SST, suggesting that there is an underlying response of increased primary production to lower temperatures. Likely mechanisms are that upwelling brings nutrients up from depth, or that Ekman flow forces freshwater farther offshore, simultaneously introducing nutrients into the offshore region and providing a more stable water column allowing production.

The physics of New Zealand’s shelf seas: introduction to the special issue - Craig L. Stevens; Joe O’Callaghan; Stephen M. Chiswell; Moninya Roughan (New Zealand Journal of Marine and Freshwater Research, 2021)

Physical oceanography of New Zealand/Aotearoa shelf seas – a review - Craig L. Stevens; Joanne M. O’Callaghan; Stephen M. Chiswell; Mark G. Hadfield (New Zealand Journal of Marine and Freshwater Research, 2021)
The shelf seas surrounding New Zealand/Aotearoa, a region nominally extending out to the 250 m depth contour, are complex and varied as they sit above the submerged continent of Zealandia. These seas surround the two main islands that span 1,500 km in latitude from 34°S to 47°S and include a series of plateaus that extend far beyond. This review summarises the present state of knowledge of the physical processes that control ocean transport and mixing in this domain. The focus is on documenting recent regional advances in understanding the balance between off‐shelf drivers, terrestrially sourced freshwater, winds, tides, stratification and the underlying topography. The review considers outstanding themes such as connectivity, climate and stratification and closes with an assessment of the potential future for understanding the physical marine environment of the shelf seas of the New Zealand region.

Circulation in Tasman‐Golden bays and Greater Cook Strait, New Zealand - Stephen M. Chiswell; Craig L. Stevens; Helen S. Macdonald; Brett S. Grant; Olivia Price (New Zealand Journal of Marine and Freshwater Research, 2021)
Analyses are presented of model simulations and Lagrangian drifter experiments designed to quantify circulation and dispersal in Tasman and Golden Bays, and their connection to Cook Strait, New Zealand. Observations made in autumn 2017 and summer 2018 are compared with numerical model results. The drifter experiments were focussed on three repeat experiments in each bay designed to measure the local horizontal eddy diffusivity. An additional experiment investigated the connection with, and flow through, Greater Cook Strait. Point by point velocities extracted from the model show low correlation with, but on average are in the same direction as observed velocities. Eddy diffusivities computed from the drifter experiments are highly variable, but the observations support the modelling. We find that the mean velocity in Tasman and Golden Bays is weak and the circulation is dominated by wind and tidal flows. The mean depth‐averaged velocity shows anticyclonic flows in the south of both Tasman and Golden Bays, with cyclonic flow in the north of Golden Bay. The mean near‐surface velocity is generally out of each bay and is compensated for by inward circulation at depth.

Relationships between long‐term ocean warming, marine heat waves and primary production in the New Zealand region - Stephen M. Chiswell; Philip J. H. Sutton (New Zealand Journal of Marine and Freshwater Research, 2020)
We test the paradigm that in a future warmer ocean, shallower winter mixing will lead to less net primary production (NPP), by investigating whether warming between 2002 and 2018 led to changes in NPP in the Tasman Sea/New Zealand region. The 2002–18 trend in sea surface temperature (SST) was positive over most of the region, and was driven by increasingly warmer summers and marine heat waves (MHWs) rather than year‐round warming. In contrast, the trends in sea surface chlorophyll (SSC) and NPP were generally positive over the Subtropical Front (STF) and in a subtropical band north‐east of New Zealand, but negative elsewhere. Regressions between SSC and SST, and between spring SSC and the coldest SST during the preceding winter, show similar spatial patterns to the SSC trend. We suggest these findings reflect different ecosystem functioning in the subtropical and subantarctic biomes that are separated by the STF. We conclude that any future warming is likely to lead to less production in the Tasman Sea, but more production over the STF. Three recent MHWs had different impacts on production, but generally led to less surface biomass north of the STF and more biomass south of the front.

Climate change projections for the surface ocean around New Zealand - Cliff S. Law; Graham J. Rickard; Sara E. Mikaloff‐Fletcher; Matt H. Pinkerton; Erik Behrens; Steve M. Chiswell; Kim Currie (New Zealand Journal of Marine and Freshwater Research, 2018)
The future status of the surface ocean around New Zealand was projected using two Earth System Models and four emission scenarios. By 2100 mean changes are largest under Representative Concentration Pathway 8.5 (RCP8.5), with a +2.5°C increase in sea surface temperature, and decreases in surface mixed layer depth (15%), macronutrients (7.5–20%), primary production (4.5%) and particle flux (12%). Largest macronutrient declines occur in the eastern Chatham Rise and subantarctic waters to the south, whereas dissolved iron increases in subtropical waters. Surface pH projections, validated against subantarctic time‐series data, indicate a 0.335 decline to ∼7.77 by 2100. However, projected pH is sensitive to future CO 2 emissions, remaining within the current range under RCP2.6, but decreasing below it by 2040 with all other scenarios. Sub‐regions vulnerable to climate change include the Chatham Rise, polar waters south of 50°S, and subtropical waters north of New Zealand, whereas the central Tasman Sea is least affected.

Wind‐driven upwelling and surface chlorophyll blooms in Greater Cook Strait - Stephen M. Chiswell; John R. Zeldis; Mark G. Hadfield; Matthew H. Pinkerton (New Zealand Journal of Marine and Freshwater Research, 2017)
We present the results of a combined observational and numerical study to investigate cool plumes of nutrient‐rich upwelled water that emanate near the Kahurangi Shoals and extend into Greater Cook Strait. Surface temperature and chlorophyll are mapped using satellite observations to produce surface climatologies, to validate a numerical simulation and to show the utility of using spatial temperature differences as a measure of upwelling. We find upwelling near the Kahurangi Shoals is strongly wind‐driven in the weather band. Upwelling occurs at all times of the year, but its surface signature is only visible in summer months. The upwelled nutrient‐rich water supports increased primary production compared to surrounding waters, particularly in summer when the water column is more stratified and surrounding surface waters are presumably nutrient depleted.

Drifter‐ and float‐derived mean circulation at the surface and 1000 m in the New Zealand region - Stephen M Chiswell; Philip JH Sutton (New Zealand Journal of Marine and Freshwater Research, 2015)
Global Drifter Program (GDP) drifter data and Argo float data from 2006 to 2013 are used to provide quantitative description and comparison of the mean near‐surface (15 m) and 1000 m velocity fields in the New Zealand region. These fields are estimated both from bin‐averaging the drifter/float velocities and by fitting non‐divergent streamfunctions to the velocities. At both levels, our velocity fields are broadly consistent with previous drifter/float estimates, but provide more detail on the local structure of the mean fields. North of the Subantarctic Front there are large differences between the surface and 1000 m flows, with the Tasman Front being largely absent at 1000 m. South of the Subantarctic Front, where the flow is expected to be more barotropic, there is a closer correspondence between the flows at both levels. Several previously undocumented eddies in the mean flows at both levels are described.

Physical oceanography of the deep seas around New Zealand: a review - Stephen M Chiswell; Helen C Bostock; Philip JH Sutton; Michael JM Williams (New Zealand Journal of Marine and Freshwater Research, 2015)
We review the advances in ‘blue water’ physical oceanography of the seas around New Zealand since the last major review in 1985. By 1985, a basic description had been made of the circulation around New Zealand. Since then, dramatic increases in data from satellites, hydrographic cruises, surface drifters and profiling floats have improved knowledge on the locations, strengths and variability of the currents, water masses and fronts in the region. We have better estimates of the surface and deep circulation, and a better understanding of the dynamical processes driving this circulation and its variability. This review covers the open ocean, including water masses, ocean currents, tides and numerical modelling, and discusses the future of New Zealand oceanography.

Absence of aggression but not nestmate recognition in an Australian population of the Argentine ant Linepithema humile - B. T. Björkman-Chiswell; E. van Wilgenburg; M. L. Thomas; S. E. Swearer; M. A. Elgar (Insectes Sociaux, 2008)

Distribution of mid‐ and late‐stage Jasus edwardsii phyllosomas: Implications for larval recruitment processes - Stephen M. Chiswell; John D. Booth (New Zealand Journal of Marine and Freshwater Research, 2005)
The relative distributions of mid‐ and late‐stage phyllosomas, and pueruli, of Jasus edwardsii from five research cruises off the east coast of the North Island of New Zealand were analysed. A statistical approach was taken, using a bootstrapping with replacement method to test whether the observed mid‐ and late‐stage phyllosomas could have come from the same distribution. Differences in distribution between mid‐ and late‐stage phyllosomas were very close to significant at 95% confidence for two cruises, significant at 85% confidence for one cruise, and two cruises showed a non‐significant result. When all cruise data were combined into one analysis, the differences between mid‐ and late‐stage phyllosomas were significant with 85% confidence. On average, late‐stage phyllosomas were found 49 km further inshore than mid‐stage phyllosomas. One station during one cruise and one transect during another showed such high abundances that they affected the analyses. When these outlier data were excluded, the differences in mid‐and late‐stage distributions become significant with 99% confidence. One explanation for observed distribution differences is that the late‐stage phyllosomas swim shoreward—as the pueruli are believed to do. This implies an ability to navigate in both these early life forms. If the late‐stage larvae are indeed swimming horizontally, it is likely that this is most effectively accomplished by final‐stage phyllosomas, which have well developed pleopods, similar to those in the puerulus stage.

Vertical distribution and diurnal migration patterns of Jasus edwardsii phyllosomas off the east coast of the North Island, New Zealand - Russell W. Bradford; Barry D. Bruce; Stephen M. Chiswell; John D. Booth; Andrew Jeffs; Simon Wotherspoon (New Zealand Journal of Marine and Freshwater Research, 2005)
The rock lobster Jasus edwardsii forms the basis of important fisheries in south‐eastern Australia and New Zealand. Their long pelagic larval phyllosoma phase (12–24 months) raises many questions as to how the larvae are retained and/or recruited into local populations. Recent attempts to model the dispersal of J. edwardsii phyllosoma have had mixed success at reconstructing settlement patterns. However, these models have either ignored vertical distribution or have used that of the western rock lobster, Panulirus cygnus. We report on the vertical distribution and migration of J. edwardsii phyllosomas, collected in March/April 2003 from the Wairarapa Eddy off the east coast of the North Island, New Zealand, and provide a model to describe their vertical distribution. J. edwardsii phyllosoma were primarily recorded within the upper 100 m over similar depth ranges to those reported for other palinurid and scyllarid species. Well‐defined changes in diel vertical distribution were restricted to late‐stage larvae. Mid‐stage phyllosomas were concentrated in the upper 20 m both day and night. Late‐stage phyllosomas were concentrated in the upper 20 m during the night, but they were absent from the upper 20 m during the day and distributed primarily between 20 and 100 m. Future modelling will benefit from using larval distribution and behaviour patterns specific to J. edwardsii.

Mean and variability in the Wairarapa and Hikurangi Eddies, New Zealand - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2005)
The mean and variability of the circulation off the east coast of the North Island, New Zealand are investigated using shipboard conductivity‐temperature‐depth (CTD) and satellite altimeter data collected between 1993 and 2003. The altimeter data are used to adjust the in situ observations for the mesoscale eddy variability before computing the 11‐year mean in dynamic height. Mean dynamic height shows two anticyclonic eddies, centred near 178.3°E, 41.2°S and 176.2°E, 42.4°S. These locations are consistent with previous historical observations of the Wairarapa and Hikurangi Eddies, respectively. A long‐term trend in both in situ and satellite data shows that dynamic height rose at an average rate of up to 2 dyn cm year ‐1 in the centre of the Wairarapa Eddy which is consistent with a strengthening of the eddy over the 11 years. The satellite data show periodic shedding of the Wairarapa Eddy from near East Cape at a rate of between two and three eddies per year. Thus, rather than indicating a permanent stationary eddy, the mean eddy reflects a region where the eddies tend to stall out or merge with the previous eddy. Often, the eddies will continue up the Hikurangi Trough so that the Hikurangi Eddy can be regarded as an older Wairarapa Eddy.

Web-building spiders attract prey by storing decaying matter - Bojun T. Bjorkman-Chiswell; Robert L. Muscat; Kim A. Nguyen; Matthew R. E. Symonds; Gina E. Westhorpe; Mark A. Elgar; Melissa M. Kulinski; Briony A. Norton (The Science of Nature, 2004)

Circulation within the Wairarapa Eddy, New Zealand - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2003)
The Wairarapa Eddy appears as a permanent anticyclonic eddy situated off the east coast of the North Island, New Zealand. In April 2001 a spatial survey of the eddy was made on a ship equipped with an Acoustic Doppler Current Profiler (ADCP). The absolute circulation at 100 m was estimated by objective mapping of the ADCP‐derived velocities to produce a velocity field that has enforced non‐divergence. Assuming that enforcing non‐divergence produces the best estimate of the geostrophic flow, this velocity field can be used as a “level of known motion” to reference geostrophic velocities at other depths. In particular, it can be used to estimate the velocity at 2000 dbar, which is otherwise used in this region as a level of no motion. The resulting flow at 2000 dbar has a mean speed of 0.07 m s ‐1 , and appears to be well correlated with the surface flow.

Temperature and salinity mean and variability within the subtropical front over the Chatham rise, New Zealand - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2002)
Estimates are made of the mean and variability in temperature and salinity across the Subtropical Front along 178°30'E, east of New Zealand. These estimates are made from six sections taken over 5 years, but biased towards spring and autumn sampling. Monte‐Carlo simulations of the potential errors introduced by this sampling suggest that the mean fields can be reasonably well determined, but the annual cycles have large relative error. April 1999 residuals were anomalously warm and saline compared with the other five sections. These anomalies may be linked to an increased strength of the Wairarapa Eddy at that time.

Wairarapa Coastal Current influence on sea surface temperature in Hawke Bay, New Zealand - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2002)
The Wairarapa Coastal Current (WCC) flows along the east coast of the North Island, New Zealand. This current has been relatively little studied, and there are few direct measurements of its mean and variability. Here, an indirect method is used to gain some insight into the WCC variability and its effect on coastal temperature. Eight years of coastal temperature from Napier in Hawke Bay are modelled as a bivariate linear expansion of alongshore windstress and solar radiation. In the frequency domain, the modelled temperatures are coherent with observed temperatures, and in the time domain, they are positively correlated for 80% of the time. The model results suggest both that variations in the WCC are wind‐driven, and that alongshore advection accounts for most of the temperature change at Napier. Periods when the modelled temperature is not correlated with observed temperature could be because of episodes of enhanced upwelling, or large‐scale influences breaking down the alongshore temperature gradient.

Determining the internal structure of the ocean off north‐east New Zealand from surface measurements - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2001)
The assumption that variability in the circulation around the east coast of the North Island of New Zealand can be described using satellite‐derived sea level and temperature and two empirical modes is tested. Potential errors are quantified if such an assumption is used to derive the internal fields from surface observations. Data from 303 CTD (conductivity‐temperature‐depth) casts made in the region between 1994 and 1999 are first tested against a much larger XBT (expendable bathythermograph) data set to show that they are representative of the expected variability, and then used to compute the empirical modes. The empirical modes are not baroclinic modes, but probably represent the lateral meanderings and variations in strength of the East Auckland Current, together with the presence of Rossby waves in this region. If surface temperature and height can be measured precisely, 60–70% of the variance in the internal temperature and velocity perturbations can be explained with the model. The standard deviation of reconstructed internal temperature errors is about 0.6° near the surface and less with depth. The standard deviation in velocity errors is 5 cm s‐1.

Influence of along‐shore advection and upwelling on coastal temperature at Kaikoura Peninsula, New Zealand - Stephen M. Chiswell; David R. Schiel (New Zealand Journal of Marine and Freshwater Research, 2001)
Thermistor data from around Kaikoura Peninsula, New Zealand, show that in the synoptic band, temperature fluctuations at 1 m are coherent with the along‐shore wind with a 90° phase difference. At 5 m, however, the coherence is not as high, and the phase relationship is in the opposite sense. Along this coast, wind‐driven advection of the coastal current and upwelling have opposite effects on temperature. A simple model is developed which has along‐shore advection and upwelling terms parameterised in terms of the wind and two unknown coefficients. Solving for the coefficients shows that at 1 m, temperature variability is determined by along‐shore advection, whereas at 5 m, temperature variability is determined principally by upwelling.

Eddy energetics in the subtropical front over the Chatham Rise, New Zealand - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2001)
The Chatham Rise, which rises to a depth of 400 m immediately to the east of New Zealand, appears to constrain the latitudinal movement of the Subtropical Front (STF). Data from current meters moored over the Chatham Rise are used to estimate the spatial variation of mean and turbulent kinetic energies and Reynolds stresses in and around the STF. Mean currents over 8 months are to the east, and are stronger south of the rise. Mean speeds at 250 m south of the rise are as high as 15 cm s −1 compared to 4.5 cm s −1 north of the rise. In contrast, the eddy kinetic energy is higher to the north at 8.2 J m −3 compared to 3.3 J m −3 to the south. Short‐term current meter moorings over the crest of the rise show no coherence over length scales of 15 km for periods less than 10 days. At 250 m depth, Reynolds stresses are positive north of the rise, and negative south of it, suggesting an export of momentum away from the STF.

The Wairarapa Coastal Current - Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 2000)
A new name is proposed for the relatively cool, fresh, northwards‐directed flow along the Wairarapa coast of New Zealand. Data from two research cruises plus historical hydrocast dam are used to show that the water within this current is modified subtropical water with sources likely to be the Southland and D'Urville currents. This current has previously been known as the Canterbury Current or as an extension of the Southland Currer t, but because of its source and location, a better name is the Wairarapa Coastal Current. One‐month‐long current meter records made off the Wairarapa coast show flow continuously to the north during February 1998. Volume transports within the Wairarapa Coastal Current in February 1998 were c. 1.6 Sv off Cape Palliser, diminishing northwards as the current becomes entrained into the East Cape Curren:.

The East Cape Current and two eddies: A mechanism for larval retention? - Stephen M. Chiswell; Dean Roemmich (New Zealand Journal of Marine and Freshwater Research, 1998)
Current meters deployed near East Cape, New Zealand, for 1 year show large differences between the offshore flow and that inshore of the 1000 m isobath. Offshore, mean flows are to the south‐east, and are the East Cape Current. Inshore, mean flows are to the north‐east, indicating that there may be a persistent inshore counter current. Comparison between the offshore current meter measurements and geostrophic currents inferred from TOPEX/Poseidon altimetry shows good agreement. We use this agreement to argue that passive drifter trajectories can be modelled using the altimeter data. By simulating drifter releases into the region, and modelling their trajectories, we develop a statistical picture of likely retention times for passive drifters. Drifters can get retained in one or other of two permanent eddies: the East Cape and Wairarapa Eddies, and retention within the system can be as high as 2–3 years, but depends on release time and location. If weak‐swimming larvae such as rock lobster larvae behave as passive drifters, retention and recirculation within the eddies may provide a mechanism allowing them to survive within the system long enough to recruit as juvenile lobsters.

The East Auckland Current, 1994–95 - Basil R. Stanton; Philip J. H. Sutton; Stephen M. Chiswell (New Zealand Journal of Marine and Freshwater Research, 1997)
The East Auckland Current (EAUC) was investigated in 1994–95 using data from three CTD surveys (conductivity, temperature, depth) and moored current meters. The strength and position of the EAUC was found to be highly variable with most of the current re‐circulating around an anticyclonic eddy north‐east of North Cape—the North Cape Eddy. The position and intensity of this eddy changed resulting in complex flow patterns with a south‐east flowing EAUC not always present as a contiguous feature. The current meter data showed a high level of mesoscale variability with low spatial coherence, suggesting that the along shore correlation length scale was c. 100 km in this current system. Near North Cape, a persistent but variable counter‐current was found inshore of the EAUC. To the south‐east a permanent anticyclonic East Cape Eddy found north of East Cape appears to dominate the flow field and the genesis of the East Cape Current.

Transports across the Tasman Sea from WOCE repeat sections: The East Australian Current 1990–94 - Stephen M. Chiswell; John Toole; John Church (New Zealand Journal of Marine and Freshwater Research, 1997)
Between March 1990 and March 1994, six cruises were made by Australian, New Zealand, and United States investigators in the Tasman Sea, occupying World Ocean Circulation Experiment repeat hydrographic lines PR11 (30°S) and PR13N (43°S). The northern section was occupied five times, the southern section was occupied four times. All sections measured temperature and salinity from the ocean surface to the bottom. Baroclinic transports through these sections are highly variable, and confirm that there is considerable eddy energy in the East Australian Current. The East Australian Current, when defined to be the main southward flowing branch, has transports varying from 22.2 to 42.2 Sv, although much of this is recirculated. As a result the total transport into the Tasman Sea, between Australia and 173°E, varies from 8.0 to 25.5 Sv. When plotted as a function of season, these transports are well fit by annual‐period sinusoids, suggesting that any interannual variability is aliased by the annual cycle.